Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Novel antioxidant peptides targeting the Keap1-Nrf2 pathway discovered from Ginkgo biloba seeds protein hydrolysate: Combining virtual screening, quantum chemical calculation, and zebrafish models in vivo validation - Mengru Yao; Yuhao Zhang; Caijing Yang; Tong Li; Haiyi Liu; Yiyun Zhao; Metsawur Memtimin; Sheng Guo; Jin-ao Duan; Ping Xiao (Food Research International, 2026)

Breaking the channel barrier: same-fluorescence, different-Tm probe strategy enables seven-target respiratory virus detection on a six-channel PCR platform within 20 minutes - Yang Li; Yi-Nuo Zhao; Xiang Li; Ting Sun; Lin-wei Zhu; Miao-jin Zhu; Li-Guo Liang; Hang-ping Yao (Analytica Chimica Acta, 2026)

Effects of dietary chitosan oligosaccharides on the laying performance, egg quality and serum biochemical parameters of aged laying hens - Zhilan Yao; Cheng Li; Ping Wu; Ping Liu (Theriogenology, 2026)

Unlocking multiscale structure-property relationships in epoxy thermosets: A machine learning-driven approach to superior multi-objective performance - Gaoming Li; Yeping Wu; Yujie Xie; Chunhua Zhu; Song Yao; Zhongtao Chen; Ping Zhang; Zixuan Luo; Xiuli Zhao; Sixun Zheng; Yinyu Zhang (Chemical Engineering Journal, 2026)

Prenatal dexamethasone exposure programs male offspring subfertility via GR/HDAC6/CTSL-mediated spermatogonial autophagic flux blockade - Shan Jin; Yixue Yao; Lu Zhu; Xiaoqi Zhao; Mengyuan Li; Ping Jiang; Ziyu Kong; Yi Liu; Ying Ao; Hui Wang (Chemico-Biological Interactions, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Making waves: Impaired osmotic reserve by chemical exposure amplifies vulnerability of estuarine organisms to climate-driven salinity shifts - Ruting Yang; Dali Wang; Yao-Ping Wang; Muting Yan; Huizhen Li; Jing You (Water Research, 2026)

Chloride ions-assisted high-efficiency natural seawater splitting enabled by noble-metal-free MnOx(OH)y/GaN nanowires - Yumeng Li; Liang Qiu; Xiantong Zheng; Lin Yao; Muhammad Salman Nasir; Zijian Huang; Ying Li; Yixin Li; Ding Wang; Wenxing Yang; Jianyang Zang; Ping Wang; et al. (Science Bulletin, 2026)

Rapid detection of raw meat freshness using deep learning and colorimetric/fluorescent array - Feiran Xu; Le Wang; Ping Li; Yang Wang; Xin Zhu; Yao Rao; Xingguang Chen; Chaofeng Li; Baocai Xu; Xuefeng Wang (Food Chemistry, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Toward high-precision, low-consumption bulk analysis: advancements in extraterrestrial sample studies - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Yong-Gang Yao; Bo Wan; Xian-Hua Li (Science Bulletin, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Groundwater-surface water interactions and material fluxes in a typical watershed, Ordos Plateau, NW China: insight from hydrochemistry, stable isotopes and 222Rn mass balance model - Wei Bao; Yixuan Wang; Ao Gao; Jiping Yao; Shen Qu; Jiajun Li; Dong Qian; Le Qiao; Lijuan Hu; Hongli Ma; Ping Miao; Haixia Wu; et al. (Environmental Geochemistry and Health, 2026)

Continental Jurassic/Cretaceous transition in Northeast China: Stratigraphic and spatiotemporal constraints from the Hailar Basin and adjacent areas - Chong-Yang Chen; Li-Ping Yao; Pu-Jun Wang; Hai-Bo Wu; Jing-Sheng Li; Yan-Ping Hou; Yun-Fei Xue; Shu-Qin Zhang (Cretaceous Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

Deep carbon recycling via the Tianshan basalt province and its contribution to Cenozoic elevated atmospheric CO2 concentration - Xiangsong Wang; Jinlong Yao; Guochun Zhao; Peter A. Cawood; Min Sun; Keda Cai; Xiao-Ping Xia; Pengfei Li; Xijun Liu; Ming Li; Yunying Zhang; Kai Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Several small reservoir islands consistently support higher taxonomic, phylogenetic, functional, and interaction diversity than few large ones across multiple taxa - Yao Shen; Yuhao Zhao; Federico Riva; Wande Li; Chen Zhu; Xue Zhang; Ping Ding; Xingfeng Si (Biological Conservation, 2026)

High-quality genome of guar (Cyamopsis tetragonoloba) provides the new insights into the biosynthesis and origination of galactomannans in Fabaceae family - Yuanhao Ding; Xinglong Zhao; Hui Yao; Shicai Huang; Xuyao Wang; Yayu Chen; Ping Li; Chengzhi Xie; Jiaquan Huang; Zhuang Yang; Haiyan Hu (Plant Cell Reports, 2026)

Allelopathy enhancement of an invasive potassium-rich plant Alternanthera Philoxeroides by potassium fertilization is caused by the increase of allelochemicals and potassium concentrations - Bing-Yao Li; Yu-Han Xiao; Wen-Qi Duan; Hong-Yu Xiao; Yan-Hong Wang; Mohamed Abdelaziz Balah; Ai-Ping Wu (Plant Ecology, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Parental DEHP exposure induces sex-specific reproductive toxicity in zebrafish and behavioral deficits in unexposed offspring - Yanan Sun; Yuqing Fan; Yao Dang; Ping Ding; Xin Li; Gang Li; Haojie Luo; Jianliang Zhao; Guocheng Hu (Environmental Pollution, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Next-generation chitosan biodegradable films reinforced with bioactive acid-DES: A sustainable solution for improved mechanical, antibacterial, and anti-browning properties - Dehong Lu; Huimin Yao; Nouman Ali Shah; Sajid Ali; Li-Yan Zeng; Ping Shi; Yuan-Sen Liu; Ziru Dai; Hafiz Umer Javed (Carbohydrate Polymers, 2026)

Impacts of diverse urbanization scenarios on typhoon precipitation patterns in the Pearl River Delta: A case study of Typhoon Mangkhut - Yongwei He; Zhongming Gao; Yulong Ma; Ping Zhou; Jingyu Yao; Xixi Yang; Lei Li (Atmospheric Research, 2026)

First report of mitochondrial genomes in Hydryphantoidea: novel genomes, evolution rate, and gene rearrangement patterns in two water mites (Acari: Hydrachnidia) - Xin-Yao Gu; Ping Li; Hao Zhong; Hai-Tao Li; Jian-Jun Guo; Gang Li; Tian-Xing Jing (Experimental and Applied Acarology, 2026)

Investigation of post-rainfall dynamic behavior of anti-dip layered rock slope through shaking table tests - Ping Hu; DeGou Cai; XianQing Xu; HongYe Yan; JunKai Yao; TaiFeng Li (Bulletin of Earthquake Engineering, 2026)

Optimizing two-stream asymmetric feature extraction architecture with dynamic re-parameterization for enhancing beef cattle weight estimation - Chong Yao; Qian Li; Ziruo Li; Tianci Mao; Xue Tian; Ping Song; Gang Liu; Miao Zhang (Computers and Electronics in Agriculture, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Metal mixture exposure and elevated risk of hypertensive disorders in pregnancy: Insights from a case-control study in northwestern China - Xueman Ding; Li Liu; Zhaochun Liu; Shurui Zuo; Yu Huang; Yizhong Yan; Shangzhi Xu; Ping Yao; Menghuan Xiao; Chengxian Dong; Chulin Yan; Xiaoyu Song; et al. (Journal of Environmental Sciences, 2026)

Structural heterogeneity and anisotropy beneath Myanmar: Insights into the complex deformation of the Indo-Burma subduction zone - Yiming Bai; Shengji Wei; Jing Chen; Tianjue Li; Bingfeng Zhang; Xiao Xiao; Shucheng Wu; Jiayuan Yao; Yu Wang; Ping Tong (Earth and Planetary Science Letters, 2026)

Functional Characterization of CsFBK, an F-Box Gene from Camellia Sinensis, Reveals its Negative Regulation of Leaf Angle in tea and Tobacco - Yongqing Bai; Bokun Zhou; Tong Li; Ping Li; Shiyu Tian; Xinzhuan Yao; Litang Lu (Journal of Plant Growth Regulation, 2026)

Dynamic response of a gentle near-fault bedrock-overburden slope after rainfall based on shaking table tests - Ping Hu; DeGou Cai; Hao Wen; HongYe Yan; JunKai Yao; TaiFeng Li (Bulletin of Engineering Geology and the Environment, 2026)

Corrigendum to “Sources of organic carbon and environmental response characteristics in the mangrove region of Trat Province, Thailand, over the past 1,019 years” [Mar. Environ. Res. 213 (2026) 107628] - Yuanqin Xu; Ping Li; Jie Liu; Wei Gao; Wenjie Yu; Yao Zhang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Marine Environmental Research, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

Establishment of an embryonic cell line of Grapholita molesta (Lepidoptera: Tortricidae) and in vitro replication of Cydia pomonella granulovirus in it - Gui-Ling Zheng; Yu-Fan Yao; Xiao-Yu Zhang; Qian-Long Yu; Jie Li; Yi-Ping Li; Dong Chu; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

A novel polyphenol-metal chelation-based structure enabling epoxy with outstanding flame retardancy, toughening effect, smoke suppression performance and recyclability - Yao Deng; Hang-Ping Fang; Qing-Qing Bi; Ying-Ming Li; De-Yi Wang (Chemical Engineering Journal, 2026)

Sources of organic carbon and environmental response characteristics in the mangrove region of Trat Province, Thailand, over the past 1,019 years - Yuanqin Xu; Ping Li; Jie Liu; Wei Gao; Wenjie Yu; Yao Zhang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Marine Environmental Research, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Development of an integrated searching system for rapid and accurate classification of edible oils by matrix-assisted laser desorption/ionization mass spectrometry - Michael Ho-Yin Ma; Suying Li; Zhen-Yan Li; Jessie Wing-Yin Wu; Zhong-Ping Yao (Analytica Chimica Acta, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Tree-mycorrhizal types differ in their biomass response to nitrogen addition - Guoyin Chen; Yuanliu Hu; Jianping Wu; Richard P. Phillips; Jianyang Xia; Ying-Ping Wang; Dafeng Hui; Jianling Li; Xianyu Yao; Qi Deng (Soil Biology and Biochemistry, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

The ilmenite-to-TiO2: A greener way to prepare titanium dioxide by hydrometallurgical hydrochloric route - Shishun Dong; Ting Li; Zhong ping Yao; Jie Jiang (Journal of Environmental Chemical Engineering, 2025)

Synergistic photothermal-magnetic nanoplatform: Recyclable TEG-SPIONs for ultra-efficient pathogen elimination in medical wastewater - Fei Ge; Yimei Wang; Jun Ge; Guoqiang Yang; Xinxin Liu; Shuxian Hou; Xuechao Shi; Yao Xiao; Shujie Li; Weiwei Zhang; Wanzhen Li; Ping Song; et al. (Journal of Environmental Chemical Engineering, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Quercetin alleviates ethanol-induced hepatocyte senescence by interacting with glycinamide ribonucleotide transformylase - Chen Huimin; Peng Shufen; Cui Zhaoyu; Liu Jiaxin; Chen Li; Yin Xingzhu; Wu Bangfu; Zhao Ying; Wang Yu; Mo Li; Liang Chanhua; Li Dongyan; et al. (Food Research International, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

Prognostic and therapeutic implications related to glycosylation profiles of cancer-associated fibroblasts in colorectal cancer: insights from single-cell and bulk transcriptomics - Keji Chen; Huixia Huang; Zijuan Hu; Yifei Zhu; Yanxi Yao; Yaxian Wang; Jiayu Chen; Yuxue Li; Dawei Li; Ping Wei (Functional & Integrative Genomics, 2025)

Unraveling the functional complexity of the locus coeruleus-norepinephrine system: insights from molecular anatomy to neurodynamic modeling - Chun-Wang Su; Fan Yang; Runchen Lai; Yanhai Li; Hadia Naeem; Nan Yao; Si-Ping Zhang; Haiqing Zhang; Youjun Li; Zi-Gang Huang (Cognitive Neurodynamics, 2025)

Gut microbiota modulation by structurally diverse foodborne polysaccharides: In vitro fermentation and prebiotic activity evaluation - Lu Wang; Jia-hao Fan; Yao Yang; Hong-wei Qiu; He-he Li; Wen-yi Kang; Guang-ping Lv (Food Bioscience, 2025)

CsAHL20 negatively regulates epi-catechins biosynthesis under drought stress in Camellia sinensis - Yu Chen; Mingyuan Luo; Ping Li; Qi Zhao; Luo Chao; Yujie Jiao; Shiyu Tian; Xingyu Tian; Shenyuan Ye; Zhenkedai Yuan; Yilan Hu; Yongqing Bai; et al. (Plant Science, 2025)

Durability and damage mechanisms of electrolytic manganese residue-based grouting materials for seepage prevention in solid waste landfills under simulated service environments - Conggan Xu; Ping Wang; Yifu Xu; Lijun Han; Saiou Fu; Yao Qu; Yongyong Chen; Weiyu Liu; Yaoyi Wang; Zhen Qi; Jing Nie; Xuewen Lei; et al. (Journal of Environmental Management, 2025)

Organic matter from spent paper cooking liquor promotes the growth and quality of Chinese chives - Yan Liu; Yuechao Yang; Guiwei Wang; Xiaoqi Wang; Ping Wang; Shan Li; Jiahui Liu; Songyuan Wang; Yijie Bai; Yao Cheng (Journal of Environmental Chemical Engineering, 2025)

Experimental and mechanistic study on the removal of elemental mercury in coal-fired flue gas by SO2-modified activated coke within a wide temperature range - Lingxuan Chen; Guangqian Luo; Mingyu Yu; Chunhui Sun; Yi Xiao; Yongda Huang; Sheng Chen; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Fuel, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Biomass-derived organic aerogels endowed flexible polyurethane foam with excellent flame retardance, smoke suppression, bacteriostasis and enhanced mechanical property - Ying-Ming Li; Yao Deng; Hang-Ping Fang; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

An anoxic/oxic membrane bioreactor for treating saline pickle wastewater: Carrier selection, process optimization, and microbial analysis - Tingting Yao; Nuonan Shen; Li Xu; Huiqiang Li; Ping Yang (Journal of Water Process Engineering, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

Cascade regulatory mechanism of soil organic phosphorus mineralization mediated by quorum sensing signal molecules C4/C6/C8-HSL: Dynamic response based on phosphatase secretion of core species - Zhenchao Wu; Jie Kang; Liangyang Mao; Yueyi Liu; Shuo Li; Weige Yao; Ying Yang; Xiujun Tu; Yuhao Guo; Jinyu Du; Xuan Tang; Tong Yang; et al. (Chemical Engineering Journal, 2025)

Stiffness matters: Exploiting mechanotransduction to guide cellular behavior and potentiate cancer therapy - Jie Wang; Lin Long; Cheng Sun; Ping Li; Sheng Yao; Ning Wang; Jun Xiao (Chemical Engineering Journal, 2025)

Comparative Efficiency of High-Throughput Magnetic Bead Method and Polyethylene Glycol Precipitation for Viral Concentration in Sewage - Jingyi Jiang; Li Gong; Ping Yao; Jian Xu; Xujian Mao; Jia Chen; Jinyi Jiang; Xiaoqiang Li; Qiong Li; Fengming Wang (Food and Environmental Virology, 2025)

Gas Hydrate Exploration Using Deep-Towed Controlled-Source Electromagnetics in the Shenhu Area, South China Sea - Jianping Li; Zhongliang Wu; Xi Chen; Jian’en Jing; Ping Yu; Xianhu Luo; Mingming Wen; Pibo Su; Kai Chen; Meng Wang; Yan Gao; Yao Zhang (Journal of Marine Science and Engineering, 2025)
This study presents the first application of a deep-towed transmitter–receiver marine controlled-source electromagnetic (TTR-MCSEM) system for gas hydrate exploration in the Shenhu area of the South China Sea. High-resolution electromagnetic data were acquired along a 13 km transect using dynamic source–receiver offsets and a 500 A transmitter. The results reveal the following: (1) unprecedented near-seafloor resolution (20~100 m) for the precise delineation of hydrate-bearing caprock, surpassing conventional ocean-bottom electromagnetic systems; (2) laterally continuous high-resistivity anomalies (~10 Ω·m) extending from the base of the gas hydrate stability zone to the seafloor, which correlate with seismic bottom-simulating reflector (BSR) distributions and suggest heterogeneous hydrate saturation; and (3) fault-controlled fluid migration pathways that supply hydrate reservoirs and lead to seabed methane seepage at structural highs. Through 2D inversion, we show that the inverted resistivity values (~10 Ω·m) are slightly higher than those obtained from resistivity logs (~5 Ω·m). Saturation values derived from inverted resistivity exhibit remarkable consistency with well-log-based measurements. The high efficiency of the system confirms its potential for the transformative quantitative assessment of hydrate systems, seafloor massive sulfides, and marine geohazards.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Effects of heat treatment on the binding between the key aroma-active compounds in Zanthoxylum bungeanum oil and pork myofibrillar proteins (MPs) - Qin Xiang; Lijuan Yao; Jiao Zhou; Songling Li; Wei Zeng; Ping Liu (Food Chemistry, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

Enhancing food security and farmers’ profit through ratoon rice-potato rotation in central China - Longxin He; Bin Du; Li Xiong; Ping Wang; Wenxue Zhang; Muhammad Imran; Gang Sun; Fusheng Yuan; Zengbing Liu; Xiong Yao (European Journal of Agronomy, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

STING-activating pyroptotic nanoparticles for in situ pancreatic cancer vaccination and immunotherapy - Shiyi Shao; Xiaohong Chen; Yuxuan Chen; Meng Wang; Junmin Huang; Jianwei Wang; Xiazhen Yu; Xinya Li; Yao Zhang; Yuan Ping; Qida Hu; Tingbo Liang (Science Bulletin, 2025)

Livistona chinensis leaves bioorganic frame derived porous carbon material containing Fe-Nx active site as oxygen reduction electrocatalyst for zinc-air batteries - Kun Fang; Chen Ling; Yan-Fang Yao; Hao Zhang; Jia-Jie Wu; Li-Ping Si; Hai-Yang Liu (Journal of Environmental Chemical Engineering, 2025)

Ultra-low temperature removal of element mercury in coal-fired flue gas by activated carbon - Renjie Zou; Tong Sun; Guangqian Luo; Lingxuan Chen; Li Wang; Sheng Chen; Shiqing Wang; Xian Li; Ping Xiao; Hong Yao (Fuel, 2025)

Using quantitative evaluation model to assess the environmental benefits of metabolites in flax retting wastewater aerobic compost: The trade-offs of core species build the profiles of beneficial and harmful metabolites converted from lignocellulose - Ying Yang; Zhichao Yang; Jie Kang; Zhenchao Wu; Yangcun Sun; Xinbo Cao; Yuhao Guo; Xiujun Tu; Liangyang Mao; Shuo Li; Weige Yao; Jingping Ge; et al. (Chemical Engineering Journal, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Preparation, adsorption and structure of Ce doped layered manganese ion-sieve based on Li2MnO3 spatial structure - Qian Liu; Li Zhang; Yucheng Liu; Xiaoqiang Zheng; Xuna Liu; Zhongquan Zhong; Liping Wei; Qianqian Zhao; Tingting Yao; Ping Yang (Environmental Research, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Dry season dominance of salinity’s impact on hydrogen isotope fractionation in Aegiceras corniculatum mangrove lipids - Yao-Ping Wang; Zhiguang Song; Jia Xia; Zhao-Wen Zhan; Alex L. Sessions; Shaelyn N. Silverman; Yuan Gao; Guopeng Li; Ding He (Geochimica et Cosmochimica Acta, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Effects of mowing frequency on the interspecific water relationships of a walnut (Juglans regia L.)-alfalfa (Medicago sativa L.) intercropping system - Yao Wang; Chunxia He; Ping Meng; Shoujia Sun; Jinsong Zhang; Pan Xue; Jianxia Li; Jinfeng Cai (Plant and Soil, 2025)

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Large-deformation analyses of seismic landslide runout considering spatially random soils and stochastic ground motions - Shun-Ping Ren; Yang Li; Xue-Jian Chen; Po Cheng; Fei Liu; Kai Yao (Bulletin of Engineering Geology and the Environment, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Therapeutic Potential of TUBB6 Inhibition for Hematoma Reduction, Microtubule Stabilization, and Neurological Recovery in an In Vivo Model of Intracerebral Hemorrhage - Jun-Yao Huang; Qiang Ma; Ya-Jie Qi; Zhi-Yao Wang; Xiao-Guang Liu; Yi-Ming Zhu; Yu-Ping Li (NeuroMolecular Medicine, 2025)

Genome-wide identification and gene expression pattern reveal dominant digestive enzyme genes contributing to major enzyme activities during the molting cycle of the Chinese mitten crab, Eriocheir sinensis - Boxiang Zhu; Min Zhang; Mingjie Li; Kewu Pan; Ping Yao; Xin Zhang; Xugan Wu (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Identification and characterization of GRAS genes in passion fruit (Passiflora edulis Sims) revealed their roles in development regulation and stress response - Xinkai Cai; Denglin Li; Chaojia Liu; Jiayi Chen; Xiuqing Wei; Sitong Hu; Lin Lu; Shengzhen Chen; Qinglong Yao; Shiyu Xie; Xiaowen Xu; Ruoyu Liu; et al. (Plant Cell Reports, 2025)

Inactivation of Salmonella Typhimurium on mung bean seeds by combined application of microbubbles and disinfections and its effect on sprouting - Hsiu-Ling Chen; Shih-Kao Chou; Rachelle D. Arcega; Chih-Yao Hou; Jong-Shinn Wu; Chih-Tung Liu; Chun-Ping Hsiao; Li-Yun Hung; Chia-Min Lin (Food Control, 2025)

Dominant spring precipitation anomaly modes and circulation characteristics in the Tarim Basin, Central Asia - Dilinuer Tuoliewubieke; Junqiang Yao; Weiyi Mao; Ping Chen; Liyun Ma; Jing Chen; Shujuan Li (Atmospheric Research, 2025)

Experimental Study of Starting Pressure Gradient in Carbonate Gas Reservoirs - Yao Zhu; Xiao-Ping Li; Li Liao; Da-Qiang Feng; Yu-Kun Mao; Jue-Qi Li; Ke-Jie Ye; Hao Zhang (Geotechnical and Geological Engineering, 2025)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Metabolic variation and oxidative stress responses of clams (Ruditapes philippinarum) perturbed by ofloxacin exposure - Bo Zhang; Xiaotong Wang; Fanping Meng; Shuhao Du; Haiping Li; Yufan Xia; Yu Yao; Ping Zhang; Jiali Cui; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Research on effective mercury removal from flue gas over Cl/Br/I/O modified adsorbents at ultra-low temperature - Lingxuan Chen; Ruize Sun; Guangqian Luo; Tong Sun; Li Wang; Leicong Liang; Yulu Zhang; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Effects of phosphate-solubilizing fungus Aspergillus flavus AF-LRH1 on promoting phosphorus solubilization, wheat growth and soil heavy metal remediation - Kaili Xu; Xiaoyong Lv; Feixue Yue; Lan Zhang; Ping Wang; Isaac Dennis Amoah; Kuok Ho Daniel Tang; Yiqing Yao; Ronghua Li (Journal of Environmental Chemical Engineering, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Discovery of the Middle Jurassic Small Theropod Footprints in Eastern Tibet, China - Yangui Li; Huazhou Yao; Asma Tahir; Junaid Khan; William J. Foster; Ping Wang; Laishi Zhao; Zhihui An; Chuanshang Wang; Jianxiong Wang (Journal of Earth Science, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Highly effective fluorescence detection of UO22+ ions by an anionic Na/Eu heterometallic metal–organic framework with Lewis basic chelating sites - Feng Guo; Xue-Ling Han; Duo-Fu Li; Chun-Yang Li; Dong-Ping Li; Zhi-Kang Yao; Li-Ping Wang; Yong-Xiu Li (Chemical Engineering Journal, 2024)

Using CFD and machine learning to explore chaotic mixing in laminar diameter-transformed stirred tanks - Anqi Li; Yuan Yao; Xin Zhang; Yu Wan; Ping Li; Yundong Wang; Changyuan Tao; Zuohua Liu (Chemical Engineering Journal, 2024)

Mechanisms of exacerbation of Th2-mediated eosinophilic allergic asthma induced by plastic pollution derivatives (PPD): A molecular toxicological study involving lung cell ferroptosis and metabolomics - Huaqin Wei; Surui Lu; Mingqing Chen; Runming Yao; Biao Yan; Qing Li; Xiaoli Song; Mengcheng Li; Yang Wu; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Multi-scenario application of chitosan emulsions as fat replacers: Based on the regulation of chitosan hydrophobicity and emulsion rheological properties - Cheng-Zhen Nie; Yao Li; Xu-Hui Huang; Hao-Peng Wang; Xu-Song Wang; Xiu-Ping Dong; Bei-Wei Zhu; Lei Qin (Food Hydrocolloids, 2024)

Epidemiology and genetic diversity of bocavirus in wild rodents in urban areas of Guangzhou, Southern China - Xin-Yan Yao; Chao-Xiang Jia; Chang-Le Li; He-Ping Li; Kai Zhong; Jian-Wei Shao; Yue-Ying Wang (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Aged polystyrene microplastics exposure affects apoptosis via inducing mitochondrial dysfunction and oxidative stress in early life of zebrafish - Ping Ding; Chongdan Xiang; Qian Yao; Xintong Li; Jiayi Zhang; Renli Yin; Lijuan Zhang; Adela Jing Li; Guocheng Hu (Journal of Environmental Management, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Polyphenol (−)-Epigallocatechin Gallate (EGCG) mitigated kidney injury by regulating metabolic homeostasis and mitochondrial dynamics involvement with Drp1-mediated mitochondrial fission in mice - Yue-Lei Chu; Jin-Chan Pi; Yu-Fei Yao; Xuan-Ying Chen; Xiao-Ping Peng; Wen-Juan Li (Food and Chemical Toxicology, 2024)

Platelet membrane coated Cu9S8-SNAP for NIR-II photoacoustic imaging guided NO repairing acute kidney injury - Xiaojuan Hu; Danping Wu; Shijie Yao; Gongning Chen; Ping Li; Yang Chen; Wancheng Gong; Weijiao Fan; Xiaoyi Chen; Xiaozhou Mou; Yu Cai; Xianghong Yang (Chemical Engineering Journal, 2024)

Facilitating proton-coupled electron transfer for energy-efficient CO2 desorption by C@ZrO2 hollow composites - Yao Shen; Ke Wang; Lu Li; Jingkai Zhao; Jiexu Ye; Ping Chen; Xiang Gao; Shihan Zhang (Chemical Engineering Journal, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Inventorization and ecological risk assessment of tetrabromobisphenol A and hexabromocyclododecane in sediments from Guangdong coastal area of South China Sea - Xiaoxia Chen; Xin Li; Yuqing Fan; Guocheng Hu; Hang Xie; Xiaoyan Chen; Ping Ding; Yao Dang; Xiyuan Hu; Qinghua Chen (Science of The Total Environment, 2024)

The composition of soil fungal communities is more dependent on biocrust type than on shrub cover in the Mu Us Desert - Lin Xu; Chaonan Li; Wenjun Xiong; YongPing Kou; Ping Zou; Bingjie Jiao; Minjie Yao; Junming Wang; Bingchang Zhang; Xiangzhen Li (Fungal Ecology, 2024)

Comparison of Drought Stress Responses in Large- and Small-Rooted Rice Lines: Physiological, Anatomical, and Hormonal Changes - Yao Guo; Yunfeng Du; Xinze Niu; Yunjing Ma; Guoqing Song; Cougui Cao; Ping Li; Yinglong Chen; Kadambot H. M. Siddique (Journal of Plant Growth Regulation, 2024)

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

Complete genome sequence of a novel amalgavirus in sponge gourd, Luffa cylindrica - Ting Li; Zhuang-Xin Ye; Yao-Liang Huang; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2024)

Evolution of physicochemical and leaching characteristics of municipal solid waste incineration fly ash in China under ultra-low emission standard - Guangyuan Yao; Rongbin Xu; Zhu Liang; Ping Li; Ya Xu; Yuqiang Liu; Can Qian; Qifei Huang (Journal of Environmental Management, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

Evaluating the influence of high-temperature sterilization and pasteurization on volatile organic compounds in tomato stewed beef brisket: An analysis using gas chromatography-ion mobility spectrometry and multivariate statistical visualization - Jicai Bi; Chunyuan Ping; Zhuo Chen; Zhen Yang; Bian Li; Yueyue Gao; Yao Zhang; Hongju He (International Journal of Gastronomy and Food Science, 2024)

Continuous recovery of lithium and boron from Jezechake Salt Lake brine using fixed-bed adsorbers - Mengxiang Lu; Yao Miao; Ying Yang; Ping Li (Hydrometallurgy, 2024)

Photoaged polystyrene microplastics result in neurotoxicity associated with neurotransmission and neurodevelopment in zebrafish larvae (Danio rerio) - Xintong Li; Tong Zheng; Jiayi Zhang; Haibo Chen; Chongdan Xiang; Yanan Sun; Yao Dang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Research, 2024)

Karyotype analysis of Chinese chive germplasms with different ploidy levels and their evolutionary relationships - Peng-Qiang Yao; Jian-Hua Chen; Pei-Fang Ma; Li-Hua Xie; Jiang Shi; Shi-Ping Cheng (Genetic Resources and Crop Evolution, 2024)

The effect of elevation, latitude, and plant richness on robustness of pollination networks at a global scale - Xiang-Ping Wang; Jeff Ollerton; Kit S. Prendergast; Jin-Chao Cai; Ma-Yin Tong; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Arthropod-Plant Interactions, 2024)

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

Combined neurotoxicity of aged microplastics and thiamethoxam in the early developmental stages of zebrafish (Danio rerio) - Yanan Sun; Ping Ding; Jiayi Zhang; Kexin Sun; Xintong Li; Qing Ge; Yao Dang; Yunjiang Yu; Guocheng Hu (Environmental Pollution, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Assessment of the combined vulnerability to droughts and heatwaves in Shandong Province in summer from 2000 to 2018 - Ping Yao; Baohuan Zhang; Ruihan Yang; Xiaonuo Ma; Xiangning Zhang; Tianxiao Wu; Baofu Li (Environmental Monitoring and Assessment, 2024)

Ginsenoside Rg1 Alleviates Sepsis-Induced Acute Lung Injury by Reducing FBXO3 Stability in an m6A-Dependent Manner to Activate PGC-1α/Nrf2 Signaling Pathway - Rong Liu; Qiang Wang; Yao Li; Ruixue Wan; Ping Yang; Dexing Yang; Jiefu Tang; Jiafei Lu (The AAPS Journal, 2024)

Experimental and computational investigation of chaotic advection mixing in laminar rectangular stirred tanks - Anqi Li; Yuan Yao; Xiaoyu Tang; Peiqiao Liu; Qian Zhang; Qian Li; Ping Li; Feng Zhang; Yundong Wang; Changyuan Tao; Zuohua Liu (Chemical Engineering Journal, 2024)

Seasonal variations and size-dependent distribution of heavy metals in particulate matter in Huangshi: Implications for human health risk assessment - Yuhu Xie; Yao Mao; Ping Zhong; Yong Zhang; Li Zhang; Wei Chen; Chengkai Qu; Xinli Xing; Junji Cao; Jiaquan Zhang (Atmospheric Environment, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Persistence of fertilization effects on soil organic carbon in degraded alpine wetlands in the Yellow River source region - Peng Duan; Rongyi Wei; Fangping Wang; Yongxiao Li; Ci Song; Bixia Hu; Ping Yang; Huakun Zhou; Buqing Yao; Zhizhong Zhao (Journal of Mountain Science, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Mediation of the JNC/ILC2 pathway in DBP-exacerbated allergic asthma: A molecular toxicological study on neuroimmune positive feedback mechanism - Xiaomin Xie; Yan Li; Biao Yan; Qi Peng; Runming Yao; Qihong Deng; Jinquan Li; Yang Wu; Shaohui Chen; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2024)

Response of mangrove development to paleoclimate variation over the past 3,550 years in Phang Nga Province, Thailand - Yuanqin Xu; Ping Li; Jie Liu; Yao Zhang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Wei Gao (Journal of Asian Earth Sciences, 2024)

Comparative study of volatile flavor compounds in green onion (Allium fistulosum L.) processed with different cooking methods - Jicai Bi; Bian Li; Zhuo Chen; Zhen Yang; Chunyuan Ping; Yueyue Gao; Yao Zhang; Lingwen Zhang (International Journal of Gastronomy and Food Science, 2024)

Dynamic, synergistic, and optimal emissions and kinetics of volatiles during co-pyrolysis of soil remediation plants with kaolin/modified kaolin - Zhibin Chen; Weijie Li; Shengzheng Huang; Ping Zhuang; Dajie Jia; Fatih Evrendilek; Sheng Zhong; Yoshihiko Ninomiya; Zuoyi Yang; Yao He; Wuming Xie; Jingyong Liu; et al. (Chemical Engineering Journal, 2024)

Charge-reversal biodegradable nanoplatform with ferroptosis and ICD induction for tumor synergistic treatment - Ping Sun; Li Huang; Zimu Li; Yao Yang; Shiman Lu; Nansha Gao; Hongzhong Chen; Xiaowei Zeng; Zhongjian Xie (Chemical Engineering Journal, 2024)

Emissions of polycyclic aromatic hydrocarbons in PM2.5 emitted from motor vehicles exhaust (PAHs-PM2.5-MVE) under the plateau with low oxygen content - Qinzuo Yao; Jianwu Shi; Xinyu Han; Senlin Tian; Jianhong Huang; Yingjie Li; Ping Ning (Atmospheric Environment, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

The IL-31/TRPV1 pathway mediates allergic asthma exacerbated by DINP dermal exposure in OVA-sensitized Balb/c mice - Qi Peng; Yang Wu; Yan Li; Chan Lu; Runming Yao; Siyuan Hu; Ning Ma; Shaohui Chen; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Layered double hydroxide@zeolite composite modified sponge: A versatile biocarrier for enhancing nitrogen removal in biofilters - Zhuwu Jiang; Mengfan Wu; Panyang Gu; Wenzhong Huang; Chang-Ping Yu; Zhongjian Zheng; Yanqu Wang; Ning Yao; Yan Li (Chemical Engineering Journal, 2024)

Revealing the molecular basis regulating the iron deficiency response in quinoa seedlings by physio-biochemical and gene expression profiling analyses - Yao Zhao; Zhangyi Chen; Weimin Li; Fei Liu; Liangliang Sun; Min Wu; Ping Zhang; Leiping Hou; Meilan Li; Jin Xu (Plant and Soil, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Experimental and numerical investigation of the expansion mechanism of beam-end expansion devices in large-span bridge - Tao Liao; Juan Song; Jun Lai; Kai Wang; Ping Wang; Zhiheng Li; Jingmang Xu; Yao Qian; Junke Lin (Engineering Structures, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Facilitating winter wheat sustainable intensification: Effects of two limited carbon-emission cultivation patterns in China's Huang-Huai-Hai Region - Xuechen Xiao; Juan Kang; Huawei Li; Yang Liu; Chunsheng Yao; Zhen Zhang; Ying Liu; Wan Sun; Guozhang Kang; Zhimin Wang; Chenyang Wang; Zhengbin Zhang; et al. (Agriculture, Ecosystems & Environment, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

Regulation of renal lipid deposition in diabetic nephropathy on morroniside via inhibition of NF-KB/TNF-a/SREBP1c signaling pathway - Wenhui Zhu; Ming Chen; Yang Wang; Yao Chen; Yonggang Zhang; Yan Wang; Peng Liu; Ping Li (Chemico-Biological Interactions, 2023)

Invasive Asteraceae plants can enhance community stability by changing pollination network structure, yet cause intense pollen disturbance to native plants in an oceanic island community - Xiang-Ping Wang; Xiao Fu; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Biological Invasions, 2023)

A new sesquiterpenoid from the aconitum -derived fungus Aspergillus fumigatus M1 - Hao Ding; Jia-Peng Wang; Si-Ping Deng; Jun-Li Gan; Bing-Xian Li; Ling-Ling Yao; Sheng-Qi Zhang; Le Cai; Zhong-Tao Ding (Natural Product Research, 2023)

Modeling and optimization of Graphene Oxide (GO) membranes for nanofiltration with artificial neural networks - Haodong Yang; Zhe Chen; Yong Li; Lei Yao; Geming Wang; Quanrong Deng; Ping Fu; Shenggao Wang (Journal of Water Process Engineering, 2023)

Widespread arboreal foraging behavior in ground-dwelling birds and the urgency of life-history studies - Wande Li; Chen Zhu; Ingo Grass; Peng Han; Yao Shen; Ping Ding; Xingfeng Si (Biological Conservation, 2023)

Realgar-Induced Neurotoxicity: Crosstalk Between the Autophagic Flux and the p62-NRF2 Feedback Loop Mediates p62 Accumulation to Promote Apoptosis - Rui Feng; Jieyu Liu; Zhao Yang; Tiantian Yao; Ping Ye; Xiuhan Li; Jiaxin Zhang; Hong Jiang (Molecular Neurobiology, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

A self-assembled nanoparticle vaccine based on pseudorabies virus glycoprotein D induces potent protective immunity against pseudorabies virus infection - Xujiao Ren; Nan Cao; Linxing Tian; Wenqiang Liu; Hechao Zhu; Zhenxiang Rong; Manman Yao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Biotrophic interactions between plant and endophytic bacteria in removal of PAHs and Cd from contaminated soils enhanced by graphene oxide - Lingmei Li; Rui Liu; Jianjun Chen; Peidong Tai; Xiaoyi Bi; Ping Zou; Yajie Wang; Yao Xiao (Journal of Cleaner Production, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Green organic-inorganic coatings for flexible polyurethane foams: Evaluation of the effects on flame retardancy, antibacterial activity, and ideal mechanical properties - Ping Li; Xu-Chen Jiang; Wan-Meng Song; Li-Yao Zhang; Ying-Jun Xu; Yun Liu; Ping Zhu (Journal of Cleaner Production, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Normal fault rupture propagation in overburdened rock and its impact on the ground deformation profile based on a model experimental approach - Tianqiang Wang; Ping Geng; Junbo Chen; Peisong Li; Qi Yang; Chaofan Yao (Soil Dynamics and Earthquake Engineering, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

A transcriptional atlas of the silk gland in Antheraea pernyi revealed by IsoSeq - Jianping Duan; Shanshan Li; Zhengtian Zhang; Lunguang Yao; Xinfeng Yang; Sanyuan Ma; Nini Duan; Jiazhen Wang; Xuwei Zhu; Ping Zhao (Journal of Asia-Pacific Entomology, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

UV-aged microplastics induces neurotoxicity by affecting the neurotransmission in larval zebrafish - Chongdan Xiang; Haibo Chen; Xiaolin Liu; Yao Dang; Xin Li; Yunjiang Yu; Bei Li; Xintong Li; Yanan Sun; Ping Ding; Guocheng Hu (Chemosphere, 2023)

Novel function of a putative TaCOBL ortholog associated with cold response - Fang-Fang Liu; Ying-Xiu Wan; Wen-Xin Cao; Qi-Qi Zhang; Yao Li; Yan Li; Ping-Zhi Zhang; Hong-Qi Si (Molecular Biology Reports, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Insights into the shift of microbial community related to nitrogen cycle, especially N2O in vanadium-polluted soil - Xuna Liu; Lina Pang; Yao Yue; Hongna Li; Efthalia Chatzisymeon; Yuanyuan Lu; Ping Yang (Environmental Pollution, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

Carbon nanofibers with gas selective layer containing rich and accessible ultramicropores for methane/nitrogen separation - Tian-Yi Li; Yong-Sheng Wang; Meng-Yao Zhang; Bo-Yang Liu; Zhe Zheng; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

Stable isotope and elemental profiles determine geographical origin of saffron from China and Iran - Jing Nie; Jian Yang; Cuiling Liu; Chunlin Li; Shengzhi Shao; Chunxia Yao; Bilian Chen; Yi Tao; Fang Wang; Yongzhi Zhang; Karyne M. Rogers; Ping Wang; et al. (Food Chemistry, 2023)

Effect of defects in adhesive layer on the interfacial bond behaviors of externally bonded CFRP-to-concrete joints - Peng-Da Li; Yao Zhao; Yu-Fei Wu; Jian-Ping Lin (Engineering Structures, 2023)

Dual seasonal pattern for hemorrhagic fever with renal syndrome and its potential determinants in China - Chen-Long Lv; Yao Tian; Yan Qiu; Qiang Xu; Jin-Jin Chen; Bao-Gui Jiang; Zhong-Jie Li; Li-Ping Wang; Simon I. Hay; Wei Liu; Li-Qun Fang (Science of The Total Environment, 2023)

Stabilized effects of L-S cement-mixed batter pile composite foundation for existed warm frozen soil subgrade - Gao-chen Sun; Gang Yao; Jian-ming Zhang; Bo Li; Jun-qi Li; Wei-ping Lian; Yi Wei (Journal of Mountain Science, 2023)

Late Holocene glacier variations indicated by the δ18O of ice core enclosed gaseous oxygen in the central Tibetan Plateau - Jiu-le Li; Bai-qing Xu; Ning-lian Wang; Ping Yao; Xiang-ke Xu (Journal of Mountain Science, 2023)

Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat - Jun Qi; Chuan-kang Jia; Wen-wen Zhang; Hui-min Yan; Qing-yuan Cai; Xiu-ning Yao; Kuo Xu; Ying Xu; Wen-ping Xu; Guo-yuan Xiong; Mei-qi Li (Food Chemistry, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Study on axial compression performance of double steel plate-concrete composite walls with stiffening ribs and tie plates - Yue Yang; Bin Wu; Yang-Ping Yao; Li-Yan Xu; Dong Zhang; Song-Han Wang (Engineering Structures, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Prenylated coumarins from the fruits of Artocarpus heterophyllus with their potential anti-inflammatory and anti-HIV activities - Lei Tao; Ya-Ting Zhuo; Ze-Hua Qiao; Juan Li; Hao-Xuan Tang; Qiao-Mei Yu; Yun-Yao Liu; Yan-Ping Liu (Natural Product Research, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto - Yang Xie; Xiao-Chang Yao; Lei-Hong Tan; Hong-Ping Long; Ping-Sheng Xu; Jing Li; Gui-Shan Tan (Natural Product Research, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Triaxial mechanical properties and micro mechanism of fiber-modified cement soil - Yang Yao; Na Li; Haibo Kang; Wenjie Yu; Chen Zhang; Ping Jiang; Wei Wang (Arabian Journal of Geosciences, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Sucrose fatty acid esters: synthesis, emulsifying capacities, biological activities and structure-property profiles - Yinglai Teng; Scott G. Stewart; Yao-Wen Hai; Xuan Li; Martin G. Banwell; Ping Lan (Critical Reviews in Food Science and Nutrition, 2021)

Effects of Low Temperature on Shrimp and Crab Physiology, Behavior, and Growth: A Review - Xianyun Ren; Qiong Wang; Huixin Shao; Yao Xu; Ping Liu; Jian Li (Frontiers in Marine Science, 2021)
As important aquaculture species worldwide, shrimps and crabs are thermophilic animals with a feeble thermoregulation ability. Changes in environmental factors are the main reason for the decrease in the immunity and disease resistance ability of cultured organisms. Water temperature is one of the most common abiotic stress factors for aquatic ectotherms. It influences nearly all biochemical and physiological processes in crustaceans, resulting in an imbalance in ion and water homeostasis, neuromuscular function loss, cellular dehydration, and altered metabolic pathways. The present review summarizes the current knowledge on the effects of low temperature on the physiological response, and the behavior, development, and growth of shrimp and crab. We suggest a deeper research to understand the physiological processes involved in thermoregulation; this knowledge could be used to reduce the adverse effects in the shrimps and crabs during the culture.

Metabolic cold adaptation in the Asiatic toad: intraspecific comparison along an altitudinal gradient - Song Tan; Ping Li; Zhongyi Yao; Gaohui Liu; Bisong Yue; Jinzhong Fu; Jingfeng Chen (Journal of Comparative Physiology B, 2021)

Cuff-less blood pressure estimation from photoplethysmography signal and electrocardiogram - Li-Ping Yao; Zhong-liang Pan (Physical and Engineering Sciences in Medicine, 2021)

Nutrigenomics reveals potential genetic underpinning of diverse taste preference of Chinese men - Zhouhai Zhu; Junpu Mei; Silong Sun; Sheming Lu; Meng Li; Ying Guan; Ying Chen; Yuqiong Xu; Tao Zhang; Fengxue Shi; Xuemei Li; Mingming Miao; et al. (Genes & Genomics, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Numerical simulation of seasonal snow in Tianshan Mountains - Yan-run Ren; Yao-nan Zhang; Jian-sheng Hao; Yong-ping Shen; Guo-hui Zhao; Cong Li (Journal of Mountain Science, 2021)

Prevalence and Bayesian Phylogenetics of Enteroviruses Derived From Environmental Surveillance Around Polio Vaccine Switch Period in Shandong Province, China - Chenxu Zhao; Xiaojuan Lin; Feng Ji; Ping Xiong; Yao Liu; Suting Wang; Peng Chen; Qing Xu; Li Zhang; Zexin Tao; Aiqiang Xu (Food and Environmental Virology, 2020)

Association of ADH7 Gene Polymorphism with Schizophrenia in the Han Population of Northern China: a Case-Control Study - Kuo Zeng; Ya Li; Meng Gao; Yong-ping Liu; Feng-ling Xu; Xi Xia; Jun Yao; Bao-jie Wang (Journal of Molecular Neuroscience, 2020)

Characterization of the promoter of the nitrate transporter-encoding gene nrtA in Aspergillus nidulans - Yangyi Liu; Haoxiang Li; Jingyi Li; Yao Zhou; Zhemin Zhou; Ping Wang; Shengmin Zhou (Molecular Genetics and Genomics, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Biofertilizers with beneficial rhizobacteria improved plant growth and yield in chili (Capsicum annuum L.) - Jing-Yi Gou; Sheng-Zhou Suo; Kun-Zhong Shao; Qi Zhao; Dan Yao; Hui-Ping Li; Jin-Lin Zhang; Christopher Rensing (World Journal of Microbiology and Biotechnology, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Three Chemosensory Proteins Involved in Chemoreception of Oedaleus asiaticus (Orthopera: Acridoidea) - Yuan-Tao Zhou; Ling Li; Xiao-Rong Zhou; Yao Tan; Bao-Ping Pang (Journal of Chemical Ecology, 2020)

Heme oxygenase-1 regulates autophagy through carbon–oxygen to alleviate deoxynivalenol-induced hepatic damage - Zhao Peng; Yuxiao Liao; Xiaoqian Wang; Liangkai Chen; Liangliang Wang; Chenyuan Qin; Zhenting Wang; Mengyao Cai; Jiawei Hu; Dan Li; Ping Yao; Andreas K. Nüssler; et al. (Archives of Toxicology, 2020)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

Macrolide sesquiterpene pyridine alkaloids from the stems of Tripterygium regelii - Dongsheng Fan; Ting Li; Zhiyuan Zheng; Guo-Yuan Zhu; Xiaojun Yao; Zhi-Hong Jiang; Li-Ping Bai (Journal of Natural Medicines, 2019)

CFTR prevents neuronal apoptosis following cerebral ischemia reperfusion via regulating mitochondrial oxidative stress - Ya-Ping Zhang; Yong Zhang; Zhi-Bin Xiao; Yan-Bo Zhang; Jing Zhang; Zhi-Qiang Li; Yao-Bin Zhu (Journal of Molecular Medicine, 2018)

Late Quaternary tectonic activity and shortening rate of the Beiluntai fault zone in the South Tianshan, Xinjiang, NW China - Yuan Yao; He-Ping Song; Jian-Bo Chen; Shuai Li; Hai-Liang Jia (Arabian Journal of Geosciences, 2018)

Geochemistry of uranium in Chinese coals and the emission inventory of coal-fired power plants in China - Jian Chen; Ping Chen; Duoxi Yao; Wenhui Huang; Shuheng Tang; Kejian Wang; Wenzhong Liu; Youbiao Hu; Qingguang Li; Ruwei Wang (International Geology Review, 2018)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

A new method for the construction and optimization of quadrangular adaptive well pattern - Kai Zhang; Hao Zhang; Liming Zhang; Ping Li; Xiaoming Zhang; Jun Yao (Computational Geosciences, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Risk assessment and vertical distribution of thallium in paddy soils and uptake in rice plants irrigated with acid mine drainage - Xuexia Huang; Ning Li; Qihang Wu; Jianyou Long; Dinggui Luo; Ping Zhang; Yan Yao; Xiaowu Huang; Dongmei Li; Yayin Lu; Jianfeng Liang (Environmental Science and Pollution Research, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Photodegradation of gemfibrozil in aqueous solution under UV irradiation: kinetics, mechanism, toxicity, and degradation pathways - Jingshuai Ma; Wenying Lv; Ping Chen; Yida Lu; Fengliang Wang; Fuhua Li; Kun Yao; Guoguang Liu (Environmental Science and Pollution Research, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

Exogenous Diethyl Aminoethyl Hexanoate, a Plant Growth Regulator, Highly Improved the Salinity Tolerance of Important Medicinal Plant Cassia obtusifolia L. - Chunping Zhang; Ping He; Yicun Li; Yan Li; Huankai Yao; Jingyu Duan; Shijun Hu; Hui Zhou; Shuo Li (Journal of Plant Growth Regulation, 2016)

Changes and characteristics of dissolved organic matter in a constructed wetland system using fluorescence spectroscopy - Yuan Yao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Ping-ping Gao; Ying-pei Zhang; Feng Yuan (Environmental Science and Pollution Research, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

Imbalanced expression of Bcl-xL and Bax in platelets treated with plasma from immune thrombocytopenia - Jianlin Qiao; Yun Liu; Depeng Li; Yulu Wu; Xiaoqian Li; Yao Yao; Mingshan Niu; Chunling Fu; Hongchun Li; Ping Ma; Zhenyu Li; Kailin Xu; et al. (Immunologic Research, 2016)

Effects of surfactants on low-molecular-weight organic acids to wash soil zinc - Yue Chen; Shirong Zhang; Xiaoxun Xu; Ping Yao; Ting Li; Guiyin Wang; Guoshu Gong; Yun Li; Ouping Deng (Environmental Science and Pollution Research, 2016)

Tissue-specific expression, developmentally and spatially regulated alternative splicing, and protein subcellular localization of OsLpa1 in rice - Hai-ping Lu; Wei-qin Pang; Wen-xu Li; Yuan-yuan Tan; Qing Wang; Hai-jun Zhao; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Photodegradation of Mefenamic Acid in Aqueous Media: Kinetics, Toxicity and Photolysis Products - Ping Chen; Feng Liang Wang; Kun Yao; Jing Shuai Ma; Fu Hua Li; Wen Ying Lv; Guo Guang Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

CD147 promotes IKK/IκB/NF-κB pathway to resist TNF-induced apoptosis in rheumatoid arthritis synovial fibroblasts - Yue Zhai; Bo Wu; Jia Li; Xi-ying Yao; Ping Zhu; Zhi-nan Chen (Journal of Molecular Medicine, 2016)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Roles of Serine/Threonine Phosphatases in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Jing Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Functions for the cAMP/Epac/Rap1 Signaling Pathway in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Cutaneous Chromoblastomycosis Caused by Veronaea botryosa in a Patient with Pemphigus Vulgaris and Review of Published Reports - Cheng-Yao Zhu; Yan-Ping Yang; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Phototransformation of mefenamic acid induced by nitrite ions in water: mechanism, toxicity, and degradation pathways - Ping Chen; Wenying Lv; Zhiming Chen; Jingshuai Ma; Ruobai Li; Kun Yao; Guoguang Liu; Fuhua Li (Environmental Science and Pollution Research, 2015)

Association between PPAR-γ2 Pro12Ala polymorphism and obesity: a meta-analysis - Ying-shui Yao; Jie Li; Yue-long Jin; Yan Chen; Lian-ping He (Molecular Biology Reports, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Photodegradation of Ibuprofen Under UV–Vis Irradiation: Mechanism and Toxicity of Photolysis Products - Fu Hua Li; Kun Yao; Wen Ying Lv; Guo Guang Liu; Ping Chen; Hao Ping Huang; Ya Pu Kang (Bulletin of Environmental Contamination and Toxicology, 2015)

Effect of dietary Chinese tea on growth performance, disease resistance and muscle fatty acid profile of channel catfish (Ictalurus punctatus) - Yao-bei-ping Zhang; Yi-bin Zhou; Ba-yi Sang; Xiao-chun Wan; Yan-ou Yang; Jian-li Zhang; Thomas L. Welker; Keshun Liu (Aquaculture International, 2015)

Optimization of Astragalus membranaceus hairy roots induction and culture conditions for augmentation production of astragalosides - Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Wei Ma; Li-Ping Yao; Chen Feng; Xin-Xin Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Identification of Mycoplasma suis MSG1 interaction proteins on porcine erythrocytes - Yaning Zhang; Yao Zou; Peipei Ma; Hassan Mushtaq Muhammad; Yufeng Li; Ping Jiang (Archives of Microbiology, 2015)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

New eudesmane-type sesquiterpenoid from Solanum lyratum with cytotoxic activity - Xiu-Ping Nie; Fang Yao; Xi-Dian Yue; Gui-Sheng Li; Sheng-Jun Dai (Natural Product Research, 2014)

Ice thickness, volume and subglacial topography of Urumqi Glacier No. 1, Tianshan mountains, central Asia, by ground penetrating radar survey - PUYU WANG; ZHONGQIN LI; SHUANG JIN; PING ZHOU; HONGBING YAO; WENBIN WANG (Journal of Earth System Science, 2014)

Myocardial mitochondrial oxidative stress and dysfunction in intense exercise: regulatory effects of quercetin - Chao Gao; Xiaoqian Chen; Juan Li; Yanyan Li; Yuhan Tang; Liang Liu; Shaodan Chen; Haiyan Yu; Liegang Liu; Ping Yao (European Journal of Applied Physiology, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

The role of sucrose-metabolizing enzymes in pear fruit that differ in sucrose accumulation - Hu Ping Zhang; Ju You Wu; Gai Hua Qin; Gai Fang Yao; Kai Jie Qi; Li Fen Wang; Shao Ling Zhang (Acta Physiologiae Plantarum, 2014)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

The overexpression of P21-activated kinase 5 (PAK5) promotes paclitaxel-chemoresistance of epithelial ovarian cancer - Diyou Li; Xiaohong Yao; Ping Zhang (Molecular and Cellular Biochemistry, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Perifosine Induces Cell Apoptosis in Human Osteosarcoma Cells: New Implication for Osteosarcoma Therapy? - Chen Yao; Jian-jun Wei; Zu-yu Wang; Hui-min ding; Dong Li; Shi-chang Yan; Yong-jiang Yang; Zhang-ping Gu (Cell Biochemistry and Biophysics, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Modeling methane emissions from irrigated rice cultivation in C hina from 1960 to 2050 - Wen Zhang; Yongqiang Yu; Yao Huang; Tingting Li; Ping Wang (Global Change Biology, 2011)
Rice paddy is a major source of anthropogenic terrestrial methane ( CH 4 ). C hina has the second‐largest area of rice cultivation in the world, accounting for ca. 19% of the world's rice‐producing area. Recognizing the significance of C hina's rice cultivation in the global CH 4 budget, we estimated the CH 4 emissions resulting from irrigated rice cultivation in C hina from 1960 to 2050 using a CH 4 MOD model. The model estimates suggest that the annual CH 4 emissions decreased from 5.62 Tg yr −1 in 1960 to 4.13 Tg yr −1 in 1970, and this decrease was attributed to changes in water management from continuous flooding to mid‐season drainage irrigation. Since the early 1970s, the amount of CH 4 emissions gradually increased to 6.85 Tg yr −1 by 2009 because of significant improvements in crop production that led to high‐crop residue retention. Higher levels of CH 4 emissions occurred in southern C hina, where double rice cropping systems are most common. For the A1B and B1 scenarios of the IPCC Special Report on Emissions Scenarios ( SRES ), the amount of CH 4 emissions from 2010 to 2050 is predicted to increase at an average rate of 1.2 kg ha −1 yr −1 in response to global warming. Compared to 2009, the CH 4 flux is predicted to increase by ca. 14% by the late 2040s, and the increase in these emissions in northeastern C hina is estimated to become more significant than in the other rice‐growing regions of the country. Under the assumptions that the rice‐producing land area will remain the same, decrease by 25% or increase by 38% by the late 2040s, the CH 4 emissions are projected to be 7.8, 5.6 or 11.7 Tg yr −1 , respectively.

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Development, characterization, and cross-species/genera transferability of SSR markers for rubber tree (Hevea brasiliensis) - Fei Yu; Bao-Hua Wang; Su-Ping Feng; Jing-Yi Wang; Wei-Guo Li; Yao-Ting Wu (Plant Cell Reports, 2011)

Isolation of a new glycoside from starfish, Asterias amurensis Lutken, and its stimulation activity on the proliferation of the UMR106 cell - Hong-Wei Liu; Jian-Kuan Li; Da-Wei Zhang; Jing-Chao Zhang; Xue Zhang; Xiao-Hong Song; Ying Xia; Nai-Li Wang; Xin-Sheng Yao; Guo-Ping Cai (Natural Product Research, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Differential expression of N-Myc downstream regulated gene 2 (NDRG2) in the rat testis during postnatal development - Wu-Gang Hou; Yong Zhao; Lan Shen; Jie Zhao; Xue-Wu Liu; Zhen Li; Xin-Ping Liu; Li-Bo Yao; Yuan-Qiang Zhang (Cell and Tissue Research, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Molecular Cloning, Expression, and Chromosomal Mapping of the Porcine CDC-2-Like Kinase 1 (CLK1) Gene - Shui Hua Xie; Jia Qi Li; Yao Sheng Chen; Ping Gao; Hao Zhang; Ze Yue Li (Biochemical Genetics, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Group Time Delay in the Reflection of P-Polarized Electromagnetic Plane Waves at a Stratigraphic Interface - Fu-Ping Liu; Rui-Zhong Li; Jin-yao Li; Hui-Guo Chen; Chang-Chun Yang (Mathematical Geosciences, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Generation and characterization of 24 novel EST derived microsatellites from tea plant (Camellia sinensis) and cross-species amplification in its closely related species and varieties - Li-Ping Zhao; Zhen Liu; Liang Chen; Ming-Zhe Yao; Xin-Chao Wang (Conservation Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Molecular and functional comparisons of the vacuolar Na+/H+ exchangers originated from glycophytic and halophytic species - Jin-yao Li; Xiao-wei He; Li Xu; Jie Zhou; Ping Wu; Hui-xia Shou; Fu-chun Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Identification of label-retaining cells in nasopharyngeal epithelia and nasopharyngeal carcinoma tissues - Hong-Bo Zhang; Cai-Ping Ren; Xu-Yu Yang; Lei Wang; Hui Li; Ming Zhao; Hong Yang; Kai-Tai Yao (Histochemistry and Cell Biology, 2007)

Genome comparison of a novel classical swine fever virus isolated in China in 2004 with other CSFV strains - Xiangmin Li; Zhuofei Xu; Yannan He; Qinxia Yao; Keshan Zhang; Meilin Jin; Huanchun Chen; Ping Qian (Virus Genes, 2006)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

Approach to the regionalization of agricultural-pasturalization around changshan islands in northern yellow sea - Yao-guang Zhang; Li-jing Dong; Chun-ping Li (Chinese Geographical Science, 2002)

Biodiversity and conservation in the Tibetan Plateau - Zhang Bai-ping; Chen Xiao-dong; Li Bao-lin; Yao Yong-hui (Journal of Geographical Sciences, 2002)

An assessment for sustainable developing capability of integrated agricultural regionalization in China - Xue-gong Xu; Hui-ping Lin; Li-sheng Hou; Xin Yao (Chinese Geographical Science, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)